Attitudes of Anemic Primigravid Women Toward the Risks of Preterm Birth and Low Birth Weight at the Independent Midwifery Practice of Solikah, S.ST., Tulungagung Regency - Friska Oktaviana (STIKes Budi Luhur Cimahi, 2026)
Anemia during pregnancy remains a major public health concern, particularly among primigravidae. This quantitative descriptive study aimed to describe the distribution of maternal attitudes toward the risks of low birth weight (LBW) and preterm birth among anemic primigravida pregnant women. A descriptive design was employed without evaluating determinants, associations, or causal mechanisms. Data were collected at the Independent Midwifery Practice (TPMB) of Solikah, S.ST, in Tulungagung Regency. Using an accidental sampling approach, 30 anemic primigravida pregnant women in their second and third trimesters were enrolled based on confirmed hemoglobin screening (Hb < 11.0 g/dL). Data were collected using a validated 15-item Likert-scale questionnaire assessing perceptions of the risks of LBW and preterm birth (r = 0.509-0.767; Cronbach's alpha = 0.868). Scores were standardized into T-scores and categorized using a cut-off value of 50. Data were analyzed descriptively using frequency distributions and percentages. The results showed that 16 respondents (53.3%) had negative attitudes (T-score < 50), whereas 14 respondents (46.7%) had positive attitudes (T-score ≥ 50) toward anemia-related pregnancy risks. Because cognitive variables were not measured, these findings describe only the observed distribution of maternal attitudes within the sampled facility and should not be interpreted as indicators of maternal knowledge, awareness, or understanding. This study received ethical approval from the Health Research Ethics Committee (No. 135/KEPK-STIKesHAH/EC/I.DIII/2025).